Interpretable machine learning for optimization of ultrasound-assisted polysaccharide extraction using natural deep eutectic solvents: From yield enhancement to structural and antioxidant activity validation - Shulu Zhang; Jingting Han; Ruichen Gao; Yeqing Xu; Zheng Feng; Xinhui Huang; Yinze Zhong; Qingxia Wang; Xinran Yu; Siyu Chang; Meiting Jiang; Zhibin Wang; et al. (Bioresource Technology, 2026)

Comprehensive source health risks of PM2.5-bound trace metals in urban and rural areas of the North China Plain - Qingxia Ma; Shuangshuang Zou; Guoqing Zhao; Kaixin Cheng; Yunfei Wu; Renjian Zhang; Lei Gu; Xiaolei Bao; Quanzhou Han; Daiqi Ye (Atmospheric Pollution Research, 2026)

Machine learning-based diagnosis of uterine myomas and sarcomas using tumor-educated platelet transcriptomics: a retrospective multicenter study - Xudong Liu; Roujie Huang; Hua Yang; Yu Dong; Lei Li; Zhe Li; Jia Zeng; Qingxia Zhang; Yun Liu; Lei Zhang; Yidi Ma; Lin Zhang; et al. (Science Bulletin, 2026)

High-performance composite adsorbent for the identification and enrichment of fenthion and its main metabolites - Lingjun Geng; Pengwei Zhang; Qingxia Han; Haifang Wang; Jingcheng Huang; Rui Xu; Jicheng Zhao; Yemin Guo; Xia Sun; Fangling Du (Journal of Hazardous Materials, 2026)

Neuroprotective Effect of Umbelliferone Against Chemotherapy-Induced Neurotoxicity in Rats via Alteration of NF-κB, PPAR-δ, and Mitochondrial Apoptosis Pathways - Xiaohui Li; Yu Han; Han Tian; Zihui Cheng; Jingjing Zuo; Qingxia Shen (Molecular Neurobiology, 2026)

An engineered single-wavelength-excitable dual-color fluorescent probe for simultaneous imaging of polarity and viscosity dynamics during ferroptosis - Jin Yu; Jie Han; Qingxia Duan; Xiaoli Zhang; Jing Jing; Guangle Niu; Xiaoling Zhang (Analytica Chimica Acta, 2025)

Lipoprotein Subfractions Predict All-cause and Cardiovascular Mortality in CKD Patients Undergoing Hemodialysis: A Prospective Cohort Study Based on NMR Metabolomics - Qingxia Huang; Han Zhang; Ziyan Shen; Jing Chen; Xuesen Cao; Linghan Xu; Cheng Zhu; Shiqi Lv; Xixi Yu; Xiaoqiang Ding; Huiru Tang; Xiaoyan Zhang (Phenomics, 2025)

Dual-recognition strategy sensor based on GO-SELEX aptamer screening for high-specificity identification of fenthion and its major metabolites in vegetables - Lingjun Geng; Haowei Dong; Qingxia Han; Xue Huang; Jingcheng Huang; Haifang Wang; Rui Xu; Jicheng Zhao; Zhouping Wang; Shijia Wu; Ibrahim A. Darwish; Yemin Guo; et al. (Food Bioscience, 2025)

Uptake of plasmid reduces the adaptation of Shigella flexneri to disinfectants and increases transmission of antibiotic resistance genes - Xiaojun Lin; Ruiqi Han; Huishi Peng; Junwei Huang; Yanbin Xu; Qingxia Qiao; Lu Huang (International Biodeterioration & Biodegradation, 2025)

Study on Effective Phase Resolution of Xiaoyao Powder and its Anti-Mammary Hyperplasia Effect - Dai Xiaofang; Zhu Meiwei; Yan Lili; Yang Fangfang; Yang Han; Wang Rui; Guan Qingxia (Journal of Pharmaceutical Innovation, 2025)

Preliminary Study on the Structure of Fungal Communities in Artificial Reef Areas in the Northern Yellow Sea - Jiamin Yan; Yue Yue; Shengkai Lin; Hanshitong Gu; Ziyi Han; Qingxia Li; Tao Tian; Xu Wei; Zhongxin Wu (Oceans, 2025)
The construction of artificial reefs is the primary ecological project of marine ranching and one of the most important methods of creating habitats for marine organisms. To date, studies on artificial reefs have taken a macroscopic perspective, with few studies having investigated the fungal communities in artificial reefs in the North Yellow Sea. Therefore, the aim of this study was to determine the distribution patterns of seawater quality, sediment properties, and fungal communities following the placement of artificial reefs of different materials in the North Yellow Sea. A sampling survey of marine ranching in the northern Yellow Sea was conducted in August 2023. Sediment and seawater samples were collected from the stone and concrete artificial reef areas as well as from the areas without constructed reefs as a control. Research shows that the total phosphorus (TP), total nitrogen (TN), and total organic carbon (TOC) concentrations were higher in the concrete reef than that in the other two regions. We obtained 735 fungal operational taxonomic units (OTUs) which were assigned to 11 phyla and 374 genera. Significant differences in the beta-diversity of the fungal communities were found among the three sampling regions, and the dominant species varied in seawater and sediment samples from different reef areas. Ascomycota was the most abundant phylum in the seawater and sediment samples, followed by Basidiomycota. pH and dissolved oxygen (DO) emerged as the most important factors affecting fungal communities in the seawater samples, whereas mean grain size, TN, and TOC had a significant effect on the communities in the sediments, with TP and TOC playing the most critical roles. Our study compared the characteristics of fungal communities in seawater and sediments in distinct types of artificial reefs and control areas, revealing the main environmental factors affecting fungal communities, which is of great significance for protecting biodiversity and evaluating the ecological effects of artificial reef placement.

Role of intensive mariculture on CO2 absorption and carbon burial, and the carbon sink potential of Sanggou Bay, China - Tingting Han; Rongjun Shi; Zhanhui Qi; Qingxia Liu; Honghui Huang (Aquaculture, 2025)

How do natural and socio-economic factors influence the sustainable development of the ecological environment in the World Natural Heritage Sites? Evidence from the Jiuzhaigou, China - Liang Chen; Haonan Yang; Huan Huang; Ming Chang; Xinyuan Wang; Dong Han; Shiyu Liu; Yi Xiao; Dong Yao; Xin Xiang; Qingxia Yang (Journal of Cleaner Production, 2023)

NLRP7 participates in the human subcortical maternal complex and its variants cause female infertility characterized by early embryo arrest - Jian Han; Nana Zhang; Qiqi Cao; Xiaodan Shi; Congjing Wang; Ximan Rui; Jie Ding; Chun Zhao; Junqiang Zhang; Xiufeng Ling; Hong Li; Yichun Guan; et al. (Journal of Molecular Medicine, 2023)

The effect of clay type and solid wettability on bitumen extraction from Canadian oil sands - An Li; Rui Li; Ci Yan; Han Wang; Qingxia Liu; Jacob H. Masliyah; Hongbo Zeng; Zhenghe Xu (Fuel, 2023)

Effects of Seawater Temperature and Salinity on Physiological Performances of Swimming Shelled Pteropod Creseis acicula During a Bloom Period - Tingting Han; Zhanhui Qi; Rongjun Shi; Qingxia Liu; Ming Dai; Honghui Huang (Frontiers in Marine Science, 2022)
Creseis acicula is a swimming shelled pteropod species, widely distributed in the world’s oceans. In 2020, an unprecedented bloom of C. acicula was observed in Daya Bay, and lasted from June to July. To date, there is very limited information on the physiological characteristics of this species, which is essential to understand bloom dynamics. In the present study, the physiological performances of C. acicula in response to temperature (17–35°C) and salinity (18–38 ppt) were investigated. The oxygen consumption (OCR) and calcification rates (CR) of C. acicula peaked at 32 and 26°C, respectively, while ammonia excretion rate (AER) significantly increased with increasing temperature. The thermal coefficient Q 10 (respiration) of C. acicula dropped to a minimum value between 32 and 35°C, suggesting that they were in a stressful status. The O:N ratio ranged from 3.24 to 5.13, indicating that protein was the major catabolism substrate. Temperature exerted a stronger effect on the OCR and AER of C. acicula . Salinity has a more influence on CR. The preferable temperature for C. acicula ranges from 29 to 32°C, and the preferable salinity ranges from 28 to 33 ppt. Based on a comprehensive consideration, we presumed that the warmer seawater temperature around the thermal discharge area of Daya Bay nuclear power plant is a possible cause for the bloom of C. acicula .